2017
DOI: 10.1021/acs.jmedchem.6b01857
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of G Protein-Biased Dopaminergics with a Pyrazolo[1,5-a]pyridine Substructure

Abstract: 1,4-Disubstituted aromatic piperazines are privileged structural motifs recognized by aminergic G protein-coupled receptors. Connection of a lipophilic moiety to the arylpiperazine core by an appropriate linker represents a promising concept to increase binding affinity and to fine-tune functional properties. In particular, incorporation of a pyrazolo[1,5-a]pyridine heterocyclic appendage led to a series of high-affinity dopamine receptor partial agonists. Comprehensive pharmacological characterization involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 77 publications
4
91
0
Order By: Relevance
“…Bias activity for dopamine D 2 receptor Ga i1 activation/b-arrestin interaction for 10 agonists measured either by BRET or enzyme complementation. Data are redrawn from Möller et al (2017).…”
Section: E Methods To Quantify Biased Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Bias activity for dopamine D 2 receptor Ga i1 activation/b-arrestin interaction for 10 agonists measured either by BRET or enzyme complementation. Data are redrawn from Möller et al (2017).…”
Section: E Methods To Quantify Biased Signalingmentioning
confidence: 99%
“…Ligand-stabilized receptor conformations drive the selection of G protein interactions and these selections can be discerned within G protein subunit families; for instance, studies with bioluminescence resonance energy transfer (BRET) biosensors have shown that oxytocin analogs differentiate between individual G i/o family members (Ga q , Ga i1 , Ga i2 , Ga i3 , Ga oA , Ga oB ; Busnelli et al, 2012). Ligand bias between subunit members of G protein families is increasingly observed with agonists for m-opioid receptors (Ga i1 , Ga oA ; Saidak et al, 2006), dopamine receptors (Ga i1 , Ga i2 , Ga i3 , Ga oA , Ga oB ; Möller et al, 2017), and PTH receptors (Ga s , Ga q/11 , and Ga io ; Appleton et al, 2013). Signaling also results from activation of Gb subunits (activation or deactivation of adenylate cyclase, PLCs, phosphatidylinositol 3-kinase) and Gg subunits (protein kinase D) (Morris and Malbon, 1999;Vanderbeld and Kelly, 2000).…”
Section: A Receptor/g Protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studied compounds consist of an arylpiperazine subunit that is considered to be a privileged chemical structure because it can be found in a variety of pharmacologically interesting compounds capable of interacting with various counterpart cellular targets . Some of the arylpiperazines that are in use in clinics have neuroprotective activity .…”
Section: Resultsmentioning
confidence: 99%